Incorporating a mobile application to support communication about HPV testing among women and professionals: barriers and facilitators from the perspective of health professionals in a middle- and low-income setting in Argentina - Szwarc, Lucila (2024)
Introduction: The delivery of positive Human papillomavirus (HPV) test results can have a psychosocial impact and act as a barrier for women to continue the cervical cancer (CC) prevention process. A previous formative research based on a woman’s perspective indicated that a mobile app could be an acceptable and appropriate tool to help women obtain information and reduce fears related to a positive result. Based on these findings, we developed an app-based intervention that would function as a support for professionals who offer the HPV test and communicate their results. We report data on the perceptions of healthcare providers regarding the barriers and facilitators to the incorporation, in a low and middle-income context.Methods: Qualitative study based on individual semi-structured interviews with health professionals. All the professionals (n =13) took HPV and Pap test samples and provided information on HPV testing, in the public health system of Ituzaingó, Greater Buenos Aires, Argentina. The themes explored were selected and analysed using domains and constructs of Consolidated Framework for Implementation Research (CFIR).Results: Practitioners had a positive assessment of the intervention through most included constructs: adaptability, compatibility, complexity, relative advantage, belief in the validity and robustness of the intervention, innovation source and knowledge and beliefs about the intervention. However, some potential barriers were also identified including: adaptability, tensions for change, relative priority and leadership engagement. Practitioners conditioned the intervention’s success to specific adjustments of the app (weight and interface usability), legitimmated institutions’ support, and clear and sustained health authorities’ commitment and directions.Conclusion: Health professionals had a positive assessment of implementing an app to support the HPV test communication and information provision process, although they conditioned its effectiveness to specific adjustments. The results allow us to identify and develop recommendations for the app to be implemented effectively and sustained over time. The findings of this study have important implications not only for Argentina, but also for other low and middle-income countries, given that the implementation could be adapted, with the aim of improving communication between patients and health institutions in the CC prevention process.